THE CORRELATION BETWEEN READING ATTITUDE AND READING ACHIEVEMENT OF THE STUDENTS IN THE ENGLISH CLASSROOM - Meliani Sasya Andini; Tahrun; Hanni Yukamana (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Ibn Khaldun Bogor, 2024)
This study was aimed at finding out whether or not there was a significant correlation between students reading attitude and their reading achievement. The research adopts a quantitative approach. Census sampling was employed to result in 30 students. The data were collected by distributing questionnaire sheets and testing a reading test to assess students reading achievement in narrative texts. In measuring the data correlation, the researcher used Pearson-Product Moment through correlation technique using SPSS 23 program. The findings of the study showed that, there is a moderate correlation between reading attitudes and reading achievement among eleventh-grade students in the English class at Shailendra High School Palembang for the academic year 2023/2024. Keywords: Correlation, Reading Attitudes, Reading Achievement.